2002
DOI: 10.1128/mcb.22.2.480-491.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity between DNA Methyltransferases in the Maintenance Methylation of Repetitive Elements

Abstract: We used mouse embryonic stem (ES) cells with systematic gene knockouts for DNA methyltransferases to delineate the roles of DNA methyltransferase 1 (Dnmt1) and Dnmt3a and -3b in maintaining methylation patterns in the mouse genome. Dnmt1 alone was able to maintain methylation of most CpG-poor regions analyzed. In contrast, both Dnmt1 and Dnmt3a and/or Dnmt3b were required for methylation of a select class of sequences which included abundant murine LINE-1 promoters. We used a novel hemimethylation assay to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
352
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 511 publications
(385 citation statements)
references
References 30 publications
28
352
1
4
Order By: Relevance
“…4 Genomic methylation patterns may be established through cooperation among these three DNMTs. 39,40 Moreover, studies have indicated that DNMT expression is coordinated in many malignancies, 12 and DNMTs have different expression levels in variable tumors or in a tissue-specific manner. 12,13 Therefore, it is hypothesized that other DNMTs are required in silencing E-cadherin in MEC.…”
Section: Discussionmentioning
confidence: 99%
“…4 Genomic methylation patterns may be established through cooperation among these three DNMTs. 39,40 Moreover, studies have indicated that DNMT expression is coordinated in many malignancies, 12 and DNMTs have different expression levels in variable tumors or in a tissue-specific manner. 12,13 Therefore, it is hypothesized that other DNMTs are required in silencing E-cadherin in MEC.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and biochemical analyses have shown that double knockout of DNMT1 and DNMT3b diminishes most of the genomic methylation while single knock-out has limited effect on DNA methylation pattern [30]; that DNMT1 alone is insufficient to restore DNA methylation after 5-azaCdR treatment [31] and that DNMT1 can form complex with DNMT3A and 3B [32] (Fig. 1).…”
Section: Dna Cytosine-5-methyltrasferase3 Likementioning
confidence: 99%
“…Because the DNMT1 hypomorphic cell line had presumably lost the ability to interact with PCNA and therefore might not be able to fully methylate its target sequences during S phase, it might be anticipated that the cells would show an increased level of hemimethylation after depletion of WT DNMT1. We therefore measured the level of hemimethylation within three regions of the p16 locus by using an assay we have previously described that couples methylation-sensitive restriction enzyme digestion with bisulfite treatment and methylation-sensitive single-nucleotide primer extension (Ms-SNuPE) analysis (20,21). The ability of the assay to detect hemimethylation at three sites [within the 5Ј region of the p16 gene (H1), at a CpG-poor site (H2), and at a CpG-rich site in intron 1 (H3)] was first validated by using T24 cells after 24-h treatment with 5-aza-CdR (20).…”
Section: Dnmt1 Rnaimentioning
confidence: 99%